PENGARUH MANAJEMEN PAJAK, PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Nadya Mei Aulia; G. Anggana Lisiantara (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to examine the effect of tax management, profitability, liquidity, leverage, and firm size on firm value in property and real estate companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The sampling technique in this study used a purposive sampling technique. The data used is secondary data in the form of company financial statements obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The number of samples used in this study were 74 companies. The results obtained in this study are tax management, liquidity, leverage have no effect on firm value. However, profitability and firm size have a positive and significant effect on firm value.